PERSEPSI PERSONEL INSTANSI TNI DISKUAL MABESAL TERHADAP EFEKTIVITAS INTEGRASI JABATAN FUNGSIONAL DAN STRUKTURAL DALAM SATU BAGAN ORGANISASI - Pradana, Wendy Mahendra; Faeni, Dewi Puspaningtyas (SINERGI : Jurnal Riset Ilmiah, 2025)
This research investigates the perceptions of personnel within the Finance Service of the Indonesian Navy Headquarters (Diskual Mabesal) concerning the effectiveness of integrating functional and structural positions into a unified organizational framework. Employing a qualitative methodology, data were collected through in-depth interviews, direct observation, and document analysis. The study reveals a spectrum of interpretations among personnel regarding the concept of integration between functional and structural roles. A majority of respondents perceive the integration as a means to enhance operational efficiency and streamline coordination mechanisms. Nevertheless, the research also identifies several challenges, including role ambiguity, dual command structures, and regulatory constraints. In response to these findings, the study recommends the implementation of continuous socialization and capacity-building initiatives, alongside structural adjustments within the organization, to facilitate the successful realization of the integration process.